MORPHOMETRIC CHARACTERISATION OF YEWA DRAINAGE BASIN, SOUTHWEST NIGERIA - Bello Abdulganiy Abayomi,; Ajibade Tajudeen Lanre, (Malaysian Journal of Tropical Geography (MJTG), 2023)
Morphometric analysis is a prerequisite for understanding the hydrological dynamics of a drainage basin's characteristics. This study focused on the morphometric characteristics of the Yewa drainage basin using GIS. The areal, linear, and relief morphometric parameters of the drainage basin were characterised using ArcGIS. The drainage map of the study area reveals a dendritic drainage pattern with a fourth-order stream network on a 4832.40 km² area. The mean bifurcation ratio of the basin is 2.03, indicating that the geological structures do not exercise a significant influence on the drainage pattern. The drainage density of the Yewa drainage basin is 0.256km-1, indicating coarse texture, high infiltration, and permeability with thick vegetation and moderate to low relief. The elongation ratio of 0.556 and the form factor of 0.243 reveals that the basin has an elongated shape. This present study gives an account of information about drainage patterns, stream behaviour, and morphometric setting of drainage within the network that support watershed management. The significance of morphometric analysis on the hydrological characterisation is discussed, and this study's relevance in water resources management and planning has been explicated.